Toward Robotically Assisted Membrane Peeling with 3-DOF Distal Force Sensing in Retinal Microsurgery() - He, Xingchi (Conf Proc IEEE Eng Med Biol Soc, 2014)
Retinal microsurgery requires steady and precise manipulation of delicate eye tissues in a very small space. Physiological hand tremor and lack of force sensing are among the main technical challenges, limiting surgical performance. We present a system that consists of the cooperatively controlled Steady-Hand Eye Robot and a miniaturized 3-DOF force sensing instrument to address these limitations. While the robot can effectively suppress hand tremor, enable steady and precise tissue manipulation, the force sensing instrument can provide three dimensional force measurements at the tool tip with submillinewton resolution. Auditory sensory substitution is used to give the user real time force information. Evaluation experiments are conducted using artificial and biological membrane peeling phantoms. Experimental results show that the robotic assistance and force-to-audio sensory substitution can effectively control the magnitude of the tool-to-tissue force. The direction profiles of the membrane peeling forces reflect the different delaminating strategies for different membrane phantoms.